Bark harvesting systems of Drimys brasiliensis miers in the Brazilian Atlantic Rainforest - Mariot A. (2014)
© 2014, Academia Brasileira de Ciencias. All rights reserved.Drimys brasiliensis Miers, locally known as cataia or casca-de-anta, is a native tree species of the Atlantic Rainforest. Its bark is harvested from natural populations. This study examined the recovery capacity of the bark of D. brasiliensis under different bark harvesting methods, as well as the influence of these approaches on its population dynamics and reproductive biology. While none of these treatments resulted in changes in phenological behavior or the rate of increase of diameter at breast height and tree height, the removal of wider bark strips resulted in lower rates of bark recovery and higher rates of insect attack and diseases. Accordingly, the results recommend using strips of bark 2 cm wide and 2 m long, with 4 cm between strips, for effective rates of bark regrowth and for lower susceptibility to insect attack and diseases. From these studies, we concluded that D. brasiliensis has a high potential for sustainable management of its natural populations, demonstrating the possibility of generating an important supplementary income for farmers and contributing to the use and conservation of the Atlantic Rainforest.